School Financial Planning Based on Stakeholder Participation: A Case Study at SMPN 2 Rumpin - Siti Zulfah Jaelilah; Endin Mujahidin; Ahmad Sastra (Moneter: Jurnal Keuangan dan Perbankan, 2026)
School financial planning is a strategic aspect in supporting the effectiveness of educational implementation. This study aims to analyze the process, mechanisms, and stakeholder participation in financial planning at SMP Negeri 2 Rumpin. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation (RKAS, RAB, BOS reports, meeting minutes). Data were analyzed using an interactive model including data reduction, data display, and conclusion drawing. The findings reveal that financial planning is conducted systematically through stages: needs identification, budgeting preparation, RKAS finalization, and monitoring-evaluation. The participation of principals, treasurers, school committees, and BOS operators is significant; however, teacher and parent involvement needs strengthening. Major challenges include limited funds, uncertainty of BOS disbursement, and financial human resource capacity. This study confirms that transparency, accountability, and deliberative decision-making are key to effective school financial planning